Sosialisasi Budaya Organisasi dan Kewajiban Belajar, Peningkatan Kompetensi dan Motivasi serta Pelatihan Manajemen Keuangan dan Literasi Keuangan Syariah kepada Siswa dan Siswi Yayasan Al-Mutakabbir Kabupaten Bogor - Saragih, Muhammad Rizal; Rusdi, Rusdi; Ambarita, Dinar; Sadewa, Prima; Nurullah, Mawardi; Hasan, Julian Muhammad; Septiningrum, Liana Dwi; Prasetya, Eka Rima; Yudawirawan, Moh. Yuddy; Arini, Dewi Ulfah; Sujarwo, Sujarwo; Afriadi, Fiqih; Febriyanto, Fery Citra (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Community service plays a vital role in bridging the gap between academic knowledge and real-world application, particularly in fostering awareness of organizational culture, lifelong learning, and financial literacy among young generations. The urgency of this activity stems from the growing need to equip students with not only academic competence but also practical skills that enhance their personal development and readiness for future professional environments. This community service program aimed to promote organizational culture, instill a sense of continuous learning, enhance student competence and motivation, and provide training in financial management and Islamic financial literacy to the students of the Al-Mutakabbir Foundation in Bogor Regency. The program was conducted through seminars and interactive discussions, targeting a total of 50 student participants. Through engaging and participatory methods, students were introduced to key concepts and best practices in financial planning, savings, investment from an Islamic perspective, and the importance of upholding organizational values. The results demonstrated a high level of comprehension and active application of the materials discussed, as reflected in post-activity evaluations and participant feedback. The implications of this success are significant, as it indicates an increased capacity among students to manage their finances responsibly and align their behavior with positive organizational and cultural values, ultimately supporting their holistic growth and contribution to society.